Time and frequency characterization of high speed I/O data bus [electronic resource] - 397525 Huang, Jimmy Huat Since (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik - Komputer dan Mikroelektronik)) - Universiti Teknologi Malaysia, 2007